Migraciones e inserción ocupacional de los cafetaleros en Honduras - Baumeister, Eduardo; Wattel, Cor (Revista de historia., 1994)
The authors first explain the historical connections among expansion of livestock raising, peasant migrations and development of coffee production in Honduras. Subsequently, they suggest characteristics of the occupational status of coffee farmers. They also explore the participation in the production of staple grain, their combination of activities during the years, as well as occupational categories or labor relations in coffee production.